2005
DOI: 10.1300/j492v05n04_02
|View full text |Cite
|
Sign up to set email alerts
|

Fruit Yield, Plant Growth and Nutrient Status in Mango

Abstract: Fruit yield and nutrient concentration of mango (Mangifera indica L.) cultivar 'Osteen' were studied in relation to rootstocks Gomera-1 and Gomera-3 for three years. The results indicated that the Gomera-3 root system had higher nutrient uptake and transport towards the scion. Data from grafted and ungrafted Gomera-1 and Gomera-3 trees proved similar with respect to N, P, and K utilization profile, with post-harvest accumulation and a decline during flowering, P and K concentrations significantly decreasing du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…The leaf area showed the significant of differences during the two seasons of study, which the leaf area of keitt and Naomi cultivars gave a high measurable than Haydi leaf area in both seasons of study. These results are agreement with Duran-zuazu (2006) which mentioned that rootstocks have a great significant effects on scion growth and gave the greatest number of the shoots and leaves with mango trees .Also Mng'omba, et al (2010), Bhuiyan, et al (2010) and Zayan, et al (2011) added that the grafted mango varieties gave high girth (diameter) and the greatest number of leaves.…”
Section: Effect Of Rootstocks On Vegetative Growth Characteristicssupporting
confidence: 85%
See 1 more Smart Citation
“…The leaf area showed the significant of differences during the two seasons of study, which the leaf area of keitt and Naomi cultivars gave a high measurable than Haydi leaf area in both seasons of study. These results are agreement with Duran-zuazu (2006) which mentioned that rootstocks have a great significant effects on scion growth and gave the greatest number of the shoots and leaves with mango trees .Also Mng'omba, et al (2010), Bhuiyan, et al (2010) and Zayan, et al (2011) added that the grafted mango varieties gave high girth (diameter) and the greatest number of leaves.…”
Section: Effect Of Rootstocks On Vegetative Growth Characteristicssupporting
confidence: 85%
“…There are some relationships between scions and rootstocks in the grafting of fruit trees in features of vegetative, flowering and yield. The vegetative status in this concern as clearly leaf area, new branches or sprout has been the numbers, lengths and canopy definitely differed from trees especially in mango trees according to (Amin 1978;Reddy et al, 2003 andDuran Zuazu ,2006).…”
Section: Introductionmentioning
confidence: 93%
“…Olour as vigorous mango rootstock had the higest leaf nutrient content., Also, the leaf nutrient status of Alphnso on vigorous rootstock were highly significantly for N, K, Fe, Ca, Mn and Cu while levels of P were not significant affected (Kurian et al, 1996). the vigorious mango rootstocks had highly significant levels for N, k, Ca and mg (Reddy et al, 2002 andDuran-Zuazu, 2006).…”
Section: -Leaf Macro Nutrients Of the Four Tested Rootstocksmentioning
confidence: 99%
“…Also, higher K concentrations were reported in leaves of 'Golden Delicious' apple on M.7 EMLA rootstock than when propagated on other stocks (Fallahi et al, 2002). Numerous studies have demonstrated that rootstocks can affect fruit quality and scion leaf mineral concentration (Boyhan et al, 1995;Dur an-Zuazo et al, 2005;Facteau et al, 1996;Knowles et al, 1984;Kviklys et al, 2012;North and Cook, 2006;Rosati et al, 1996;Tomala et al, 2008;Tsipouridis and Thomidis, 2005;W€ unsche et al, 2005).…”
mentioning
confidence: 99%